Integration of the production and the purification processes of cutinase secreted by a recombinant Saccharomyces cerevisiae SU50 strain - Calado, Cecília (2020)
By expanded bed adsorption (EBA) it was possible to simultaneously recover and purify the heterologous cutinase directly from the crude feedstock. However, it was observed that in a highly condensed and consequently economically advantageous purification process as EBA, the cultivation step highly influences the following purification step. Thus, the yeast cultivation and cutinase purification by EBA cannot be considered as independent entities, and the understanding of the interactions between them are crucial for the development of a highly cost effective overall cutinase production process. From the cultivation strategies studied, one batch, one continuous and two fed-batch cultivations, the strategy that resulted in a more economical cutinase overall production process was a fed-batch mode with a feeding in galactose. This last cultivation strategy, exhibited the highest culture cutinase activity and bioreactor productivity, being obtained 3.8-fold higher cutinase activity and 3.0-fold higher productivity that could compensate the 40% higher cultivation medium costs when compared with a fed-batch culture with a feeding on glucose and galactose. Moreover, a 3.8-fold higher effective cutinase dynamic adsorption capacity and 3.8-fold higher effective purification productivity were obtained in relation to the fed-batch culture with the feeding on glucose and galactose. The cultivation strategy with a feeding on galactose, that presented 5.6-fold higher effective purification productivity, could also compensate the 32% effective adsorption capacity obtained with a continuous cultivation broth. Furthermore, a 205-fold higher cutinase activity, 24-fold higher bioreactor productivity and 6% of the cultivation medium costs were obtained in relation to the continuous culture.